Meningitis and procalcitonin: An integrative review (Research, Society and Development, 2024)
Meningitis are inflammatory processes of the meninges, connective structures that involve the central nervous system, and can be caused by bacterial, viral and other agents. Early diagnosis as well as its etiological distinction are essential to increase survival. Inflammatory markers such as procalcitonin, although questioned, may be useful in the early diagnosis of this disease. The aim of this study was to evaluate the effectiveness of measuring procalcitonin in biological samples for the diagnosis of acute meningitis. This is an integrative review and 17 original studies published in the last five years were included in this analysis. As a result, procalcitonin seems to have a good predictive value when measured in the CSF and its elevation has a high sensitivity for bacterial infection of the meninges. Its dosage is not available in all emergency care services, which is a limiting factor for its comparison.